Customer Relationship Management in Agile Healthcare Organizations - Nasrabad, Rafat Rezapour (International Journal of Economics and Financial Issues, 2017)
Today, several studies in the field to identify key factors in the success and agility of health care organizations to improve their performance in the face of changes have taken place in the context of customer relationship management among them. The purpose of this study was to explore the concept of customer relationship management, goals and benefits by considering its relationship with value creation for clients and treatment. Results showed concern for organizations today, creating customer satisfaction at the highest customer loyalty, which requires involvement in the value chain activities and decisions of the organization. Keywords: Management, Customer relationship, Customer Orientation, Value, Healthcare Service JEL Classifications: C32; O13; O47